Numerical and experimental investigation on the performance of the capillary tube using R-134a and R-600a (Journal of Engineering, 2012)
In this paper, isobutane (R-600a) is used as a suitable substitute for (R-134a) when changing the length of capillary tube. And the experimental data on capillary tube are obtained under different conditions such as (subcooling and ambient temperatures) on domestic refrigerator (9ft3 size), this data shows that (R-600a) a suitable substitute for (R134a) .The test presented a model for a steady state, two-phase flow in capillary tube for vapour compression system .The numerical model depends on conservation equations (mass, energy and momentum) as wall as the equation of state for refrigerant. The solution methodology was implemented by using finite difference techniques. The system results indicate that it is possible to change the refrigeration system using (R-134a) by shorter capillary tube length about (28.6%) when using (R-600a) .The theoretical results for different variables such as(subcooling and ambient temperatures) showed a good agreement with the "ASHRAE" tables and experimental results.